Pengaruh leader member exchange terhadap kinerja karyawan dengan budaya tri hita karana sebagai pemoderasi - Ketut Gunawan; Fridayana Yudiaatmaja; Nyoman Suandana; Ni Ketut Adi Mekarsari (Jurnal Ekonomi Modernisasi, 2022)
This study aims to investigate the effect of the Leader Member Exchange (LMX) on employee performance, as well as the role of tri hita karana culture as a moderator of the influence of LMX on employee performance. The research was conducted at Perumda Air Minum Tirta Hita, Buleleng Regency, where 73 employees were involved in this research. This study uses a quantitative approach and Moderate Regression analysis for data analysis. The results showed that there was a significant effect of LMX on employee performance, the tri hita karana culture had a significant effect on employee performance, and the interaction between LMX and the tri hita karana culture can strengthen employee performance. Discussions on important points in the tri hita karana culture can be adopted as a stimulus in improving LMX and employee performance at Perumda Air Minum Tirta Hita.